Time and Entropy: The Two Sides of The Same Medal in Ideal Open Systems - Horst Josef Koch (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2016)
The second thermodynamic law implies a continuous increase of entropy with time and a formal relation of both characteristics. Based on observations in ideal biophysical diffusion processes the letter presents a model that substantiates an exponential relationship between time and entropy.